Heterogeneous copper-catalyzed synthesis of diaryl sulfones. Issue 48 (1st December 2021) - Gong, Xinchi; Shen, Zhengqi; Wang, Ganghu; Qu, Lingling; Zhu, Chunyin
Abstract : A carbon-supported copper nanoparticle (Cu-NP) with high catalytic activity for the synthesis of diaryl sulfones is reported. Abstract : A carbon-supported copper nanoparticle (Cu-NP) with high catalytic activity for the synthesis of diaryl sulfones is reported. For the first time, this Cu-NP is proved to be able to effectively promote the reaction of arylboronic acids and arylsulfonyl hydrazides to generate diaryl sulfones at room temperature. The reaction shows excellent substrate universality, and substrates with different substituents can undergo the reaction smoothly, leading to the desired products in good yields. The Cu-NP is found to be made of low valence Cu based on XRD. Hence, the reaction catalyzed by the Cu-NP is believed to involve a Cu-mediated organometallic cycle.